Становлення Музею визвольних змагань та формування його колекцій: від відділу Музею НТШ до окремої музейної установи - Петрик, Наталя; Petryk, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2017)
Розглянуто процес становлення Музею визвольних змагань від етапу формування окремого відділу в рамках Музею НТШ до утворення спеціалізованого музею як окремої інституції. Висвітлено роль товариства «Молода громада» у процесі виникнення нового Музею. Розглянуто нормативно-правову базу, на основі якої мав функціо -нувати Музей. The text deals with the process of establishing the Museum of Liberation Movement or the Museum of historical and military attractions of Shevchenko Scientific Society from the forming a separate department as a structural part of the Museum of Shevchenko Scientific Society to formation a specialized museum as a separate institution (1937–1939). The role of the company «Young community» in the process of appearance of a new museum was investigated in the article. The regulatory base of the Museum of historical and military attractions was considered too. The text discusses a problem and sources of formation a collection of military and historical attractions of Museum during the first part of XX century, and the historical fate of these attractions. In the article the contribution of donors is indicated in the formation of major groups of collections. The most typical groups of attractions of military and historical collection was considered in detail in this article.
The Formation of the Museum of Liberation Movement and the Formation of its Collections (from the Department of the Museum of NTSh to a Separate Museum Institution)
Keywords: Наукове товариство імені Шевченка (НТШ); Музей визвольних змагань; товариство «Молода громада»; колекції; пам’ятки; Shevchenko Scientific Society; Museum of Liberation Movement; the company «Young community»; collection; attractions